A Visual and Bibliometric Overview of the Hedonic Hunger Literature - Kaya, Aysel Şahin (Discoveries in Agriculture and Food Sciences, 2025)
Aim: This study sought to provide an overview of the hedonic hunger research community using bibliometric data. Material and methods: The Web of Science (WoS) Core Collection was searched for all current and highly cited hedonic hunger research articles published in English between January 1, 1970 and July 31, 2024 for this bibliometric study. Using abstracts and full texts when necessary, the titles that were found were evaluated for eligibility. In addition to journals, authors, and countries of eligible articles, it was also identified keywords categories to track publication trends. On the basis of published data, the number of citations for each eligible article was compared to the expected number. Results: A total of 1,966 articles from various fields make up the dataset. Nutrition and dietetics (41.506%), behavioral sciences (24.364%), and psychology (23.093%) are important fields. Publications started in 1992 increased after 2009, reaching a peak of 178 with 9,022 citations in 2021. Contributors also include Yale University (2.95%), Oregon Research Institute (3.001%), and Maastricht University (3.357%). The United States (901 documents, 43,113 citations), England (302 documents, 13,226 citations), and Germany (185 documents, 7,282 citations) are the top three nations. Conclusion: This study shows a dynamic research landscape in the area of hedonic hunger that reflects cross-disciplinary cooperation and a worldwide perspective. The increase in publications and citations, significant works, and active collaborations all highlight the value of global cooperation in furthering scholarly work.